Sensitivity of Lymph Node Aspiration in Localized Cutaneous Leishmaniasis Due to Leishmania (Viannia) braziliensis - Romero, Gustavo Adolfo Sierra (1999)
Twenty nine patients with localized cutaneous leishmaniasis had lymph node and skin ulcer aspirations for culture of Leishmania with the modified Marzochi´s vacuum aspiratory technique. Sensitivity of lymph node aspiration was 58.6% and 34.5% for skin ulcer aspiration (P=0.06). Combined sensitivity of the two methods was 79.3%. There was no agreement between methods (Kappa Index = -0.084; CI95% -0,45; 0,28) showing the potential complementary roles in diagnostic approach.